Relation between mechanical properties of cork from Quercus suber - Anjos, O. (2008)
Cork is known as the material used for the production of wine stoppers. The specific properties of cork, e.g. low density, very low permeability to water, elastic properties and inertness have made it the best sealant for quality wine. Here we studied the relation between compression, tensile and bending stress in cork and the influence of structural characteristics of cork on its mechanical behaviour. The material was sampled from raw cork planks of good quality (class 1) and poor quality (class 4) collected at one industrial mill after post-harvest six-month air stabilization, water boiling and air drying as usually applied in cork industrial processing. The samples had densities ranging 0.123 - 0.203 g.cm-3 and porosities between 0.5 and 22.0%. There are differences between the type of stress and the corresponding direction of stress. For the same direction of stress, the Young modulus in tension is higher then in bending and it is lowest in compression. The bending Young modulii were well correlated with the tensile Young modulii, because while in bending the sample is submitted to both tensile and compression stresses, the fracture occurs in the tensile zone. There were no significant differences in the mechanical properties of cork samples obtained from cork planks of different quality classes but the density is an important factor and samples with higher density showed overall larger resistance. Mechanical properties were influenced by the structural features related to the lenticular channels, namely the presence of thick walled and lignified cells that may border the lenticular channels.